Pengaruh Leadership, Lingkungan Kerja, Dan Semangat Kerja Terhadap Prestasi Kerja Pegawai Dinas Badan Pendapatan Daerah Kabupaten Labuhanbatu Utara - Raja Saul Marto Hendry (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
The purpose of this study was to determine the influence of leadership, work environment and morale on the performance of employees at the Office of regional revenue Labuhanbatu North either partially or simultaneously. The sample in this study amounted to 56 people. The analysis method used is descriptive analysis, classical assumption test, multiple Linear regression analysis, T test, F test, and coefficient of determination and the data is processed using the IBM SPSS Statistics 23 program. The results of the hypothesis test showed that partially motivation has a positive and significant effect on employee performance, it is seen from the value of thitung for leadership is thitung 2.822 > ttable 2.00, with a significant value of 0.007 < 0.05. The work environment has a positive and significant effect on Employee Performance, This is seen from the value of thitung for the work environment is thitung 3.481> ttable 2.00, with a significant value of 0.001 < 0.05. Job satisfaction has a positive and significant effect on Employee Performance, This can be seen from the value of thitung for work stress is thitung 2.540> ttable 2.00, with a significant value of 0.024< 0.05. The value of Ftable is 2.76, then based on Table 4.14 it can be seen that the value of F count 11.369 >2.76, and the significant value of 0.000 < 0.05. This shows that simultaneously The Independent Variable has a positive and significant effect on the Dependent variable.